A new collation and text for EN X.6-9 [=Bywater X.6-8] - de Sousa, Victor Gonçalves (Journal of Ancient Philosophy, 2024)
In this paper, I attempt to explore a recent hypothesis about what the main mss. are for establishing the text of Aristotle’s Ethica Nicomachea (henceforth EN). This hypothesis was recently advanced on the basis of evidence coming from EN I-II. In exploring this hypothesis, I confine myself to the text of EN X.6-9 [=Bywater X.6-8], and, as a result, I propose a new text for EN X.6-9 [=Bywater X.6-8] based on a fresh collation of nine mss—four of which were not taken into account in previous editions of the EN—and based on readings that can be gathered from the Arabic translation of the EN that was preserved in the Fez ms. The text proposed in this paper is accompanied by textual notes that justify my decisions regarding some difficult passages.